Explaining variation in referral from primary to secondary care: cohort study. (30th November 2010) - McBride, Dulcie; Hardoon, Sarah; Walters, Kate; Gilmour, Stuart; Raine, Rosalind
Abstract : Objectives To determine the extent to which referral for defined symptoms from primary care varies by age, sex, and social deprivation and whether any sociodemographic variations in referral differ according to the presence of national referral guidance and the potential of the symptoms to be life threatening. Design Cohort study using individual patient data from the health improvement network database in primary care. Setting United Kingdom. Participants 5492 patients with postmenopausal bleeding, 23 121 with hip pain, and 101 212 with dyspepsia from 326 general practices, 2001-7. Main outcome measures Multivariable associations between odds of immediate referral for postmenopausal bleeding and age and social deprivation; hazard rates of referral for hip pain or dyspepsia and age, sex, and social deprivation. Analyses for dyspepsia were stratified for people aged less than and more than 55 years because referral guidance differs by age. Results 61.4% (3374/5492) of patients with postmenopausal bleeding, 17.4% (4019/23 121) with hip pain, and 13.8% (13 944/101 212) with dyspepsia were referred. The likelihood of referral for postmenopausal bleeding declined with increasing age: the adjusted odds ratio for patients aged 85 or more compared with those aged 55-64 was 0.39 (95% confidence interval 0.31 to 0.49). Patients aged 85 or more with hip pain were also less likely to be referred than those aged 55-64 (0.68, 0.57 to 0.81). Women were less likely than men to be referred for hip pain (hazard ratio 0.90, 95% confidence interval 0.84 to 0.96). More deprived patients with hip pain or dyspepsia (if aged <55) were less likely to be referred. Adjusted hazard ratios for those in the most deprived Townsend fifth compared with the least deprived were 0.72 (95% confidence interval 0.62 to 0.82) and 0.76 (0.68 to 0.85), respectively. No socioeconomic gradient was evident in referral for postmenopausal bleeding. Conclusions Inequalities in referral associated with socioeconomic circumstances were more likely to occur in the absence of both explicit guidance and potentially life threatening conditions, whereas inequalities with age were evident for all conditions.